Developing the Case Method Module on the Environmental Management to Improve Student’s 21st-Century Skills - Diah Anugrah Dipuja; Resma Wahyuni; Ayu Maysaroh (Department of Biology Education Faculty of Teacher Training and Education Sebelas Maret Un, 2025)
The limited variety of learning methods and teaching materials used in environmental management material affects students' 21st-century skills. Current learning is still conventional and ignores the development of 21st-century skills, which include critical thinking, creativity, communication, and collaboration. This research aims to produce a case method-based environmental management module to improve students' 21st-century abilities that is valid, practical, and effective. The research was conducted in June-October 2023 at Riau University. The research sample included students from the marine science study program who took Environmental Science courses. This type of research is development using the ADDIE model. The research instruments used validation sheets, observation sheets, and response questionnaires. The average validation result for the module is 3.64, with a very valid category. The results of the response questionnaire in the limited trial obtained an average score of 3.82 in the very valid category, while the results of the practicality questionnaire received a score of 85% in the practical category. The observation results obtained a score of 85 for the competence category. Based on the research results, it can be concluded that the environmental management-based case [R1] method improves students' 21st-century abilities, it is very valid, practical, and effective to use in learning [R1]Konsistensi penggunaan istilah/penamaan modul